Addition of Povidone-Iodine to Fluoride Varnish for Dental Caries: A Randomized Clinical Trial. (April 2021) - Milgrom, P.; Tut, O.; Rothen, M.; Mancl, L.; Gallen, M.; Tanzer, J.M.
Introduction: Dental caries is the most common chronic childhood disease. Products of metabolism by bacteria populating the tooth surface induce development and progression of cavities. Objectives: We sought to determine whether a polyvinylpyrrolidone-iodine (PVP-I; povidone-iodine) and NaF topical varnish was superior to one containing only NaF in prevention of new dental caries lesions in a single-center randomized active-controlled trial based on a double-blind, parallel-group design. Methods: The site was Pohnpei State, Federated States of Micronesia. The study population was healthy children 49 to 84 mo old who were enrolled in early childhood education: 284 were randomized (1:1 allocation), and 273 were included in year 1 analysis and 262 in year 2. The test varnish contained 10% PVP-I and 5.0% NaF. The comparator contained only 5.0% NaF but was otherwise identical. Varnishes were applied every 3 mo during 2 y. The primary outcome was the surface-level primary molar caries lesion increment (d2-4 mfs) at 2 y. Caries lesion increments from baseline to year 1 and year 2 were compared between conditions with log-linear regression, adjusting for age and sex and whether the tooth was sound at baseline (free of caries lesions). Results: At year 1, the caries lesion increment for primary molars sound at baseline was 0.9 surfaces (SD = 1.5) for the test varnish versus 1.8 (SD = 2.2) for the comparator varnish with fluoride alone (adjusted rate ratio, 0.50; 95% CI, 0.31 to 0.81; P = .005). At year 2, the caries lesion increment for primary molars sound at baseline was 2.3 surfaces (SD = 2.8) for the test varnish as compared with 3.3 (SD = 2.7) for the comparator (adjusted rate ratio, 0.74; 95% CI, 0.52 to 1.03; P = .073). Teeth that were already cavitated at baseline did not show a preventive effect. There were no harms. Conclusions: A dental varnish containing PVP-I and NaF is effective in the primary prevention of cavities in the primary dentition (NCT03082196). Knowledge Transfer Statement: This study demonstrates that periodic application of a varnish containing NaF and PVP-I is effective in prevention of caries lesions and useful in assessing the potential of combined treatment.